Educators' Perception Towards Early Childhood Education in Technology Integration: A Case Study - Akhmad Sutiyono; Tommy Hastomo; Mereyke Jessy Tanod (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The use of technology can be integrated into early childhood education to college. Several studies explain that technology can improve the learning process in early childhood education. This study aims to investigate teachers' perceptions of the integration of technology into early childhood learning. The researcher applies a case study as a research design. The data obtained are primary. The research instrument consisted of observations, interviews, and surveys where teachers of private kindergarten schools in Bandar Lampung were research respondents. The study findings show that most teachers show a positive attitude towards using technology in the classroom and have tried to integrate it into learning activities. Meanwhile, there are two obstacles to applying technology in learning English in early childhood: maintaining their attention when using technology devices in the classroom and choosing suitable technology for children